Cloning, purification, and characterization of GH3 β-glucosidase, MtBgl85, from Microbulbifer thermotolerans DAU221 - Hyo-Min Pyeon; Yong-Suk Lee; Yong-Lark Choi (PeerJ, 2019)
Background β-Glucosidases have attracted considerable attention due to their important roles in various biotechnological processes such as cellulose degradation to make energy and hydrolysis of isoflavone. Microbulbifer thermotolerans (M. thermotolerans) is isolated from deep-sea sediment and has not been researched much yet. As a potential candidate for a variety of biotechnological industries, β-glucosidases from the novel bacterial species should be researched extensively. Methods β-Glucosidase, MtBgl85, from M. thermotolerans DAU221 was purified by His-tag affinity chromatography and confirmed by SDS-PAGE and zymogram. Its biochemical and physiological properties, such as effects of temperature, pH, metal ions, and organic solvents, substrate specificity, and isoflavone hydrolysis, were investigated. Results M. thermotolerans DAU221 showed β-glucosidase activity in a marine broth plate containing 0.1% esculin and 0.25% ammonium iron (III) citrate. The β-glucosidase gene, mtbgl85, was isolated from the whole genome sequence of M. thermotolerans DAU221. The β-glucosidase gene was 2,319 bp and encoded 772 amino acids. The deduced amino acid sequence had a 43% identity with OaBGL84 from Olleya aquimaris and 35% and 32% identity with to CfBgl3A and CfBgl3C from Cellulomonas fimi among bacterial glycosyl hydrolase family 3, respectively. The optimal temperature of MtBgl85 was 50 °C and the optimum pH was 7.0. MtBgl85 activity was strongly reduced in the presence of Hg2+ and Cu2+ ions. As a result of measuring the activity at various concentrations of NaCl, it was confirmed that the activity was maintained up to the concentration of 1 M, but gradually decreased with increasing concentration. MtBgl85 showed higher enzyme stability at non-polar solvents (high Log Pow) than polar solvents (low Log Pow). The hydrolyzed products of isoflavone glycosides and arbutin were analyzed by HPLC.